Towards OER Statistics: Data Requirements for the Scientometric Analysis of Open Educational Resources - Kullmann Sylvia (Open Information Science, 2025)
The responsible research assessments initiative aims to broaden the scope of what can be recognised in science evaluation. As a scientometric approach, the open educational resources (OER) statistics framework contributes to this mission by rewarding academic teaching as a performance class via OER. Specialised OER infrastructures can be considered data providers for OER statistics. The analysis of selected OER infrastructures shows that in order to obtain comprehensive OER-related datasets that can be used for the determination of the OER statistics without significant additional effort, improvements in the metadata provided are needed. This applies to the completeness of databases, the use of persistent identifiers, and the references and attributions/citations of OER, but also to details such as information on quality, year of creation, version management, or granularity of OER.